2021
DOI: 10.1007/s10508-020-01880-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Perceived Barriers and Facilitators of PrEP Uptake among Young People in Uganda, Zimbabwe, and South Africa

Abstract: Pre-exposure prophylaxis (PrEP) is an effective HIV prevention strategy. Few studies have explored adolescents and young people’s perspectives toward PrEP. We conducted 24 group discussions and 60 in-depth interviews with males and females aged 13–24 years in Uganda, Zimbabwe, and South Africa between September 2018 and February 2019. We used the framework approach to generate themes and key concepts for analysis following the social ecological model. Young people expressed a willingness to use PrEP and identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 36 publications
(48 reference statements)
13
53
0
Order By: Relevance
“…Relationships built with other PrEP users, through virtual platforms or physical meetings, could also provide long-term social support. A high proportion of participants reported that PrEP use was facilitated by support from friends and family, in line with qualitative research done in three sub-Saharan contexts where youth perceived peer influence and social support as potential facilitators to PrEP uptake [45]. This also suggests that most participants told at least some friends and family members about PrEP.…”
Section: Discussionsupporting
confidence: 77%
“…Relationships built with other PrEP users, through virtual platforms or physical meetings, could also provide long-term social support. A high proportion of participants reported that PrEP use was facilitated by support from friends and family, in line with qualitative research done in three sub-Saharan contexts where youth perceived peer influence and social support as potential facilitators to PrEP uptake [45]. This also suggests that most participants told at least some friends and family members about PrEP.…”
Section: Discussionsupporting
confidence: 77%
“…One major challenge to acceptability of PrEP in this study, as has been noted elsewhere ( Kawuma et al, 2021 ; Muhumuza et al, 2021 ), was taking pills which are similar to those taken by people living with HIV. Hence participants preferred on-demand PrEP, largely because it would shelter them from being seen “taking pills daily".…”
Section: Discussionmentioning
confidence: 74%
“…Community-based studies of daily oral PrEP implementation in East Africa also indicate lower uptake among people younger than 25 years old ( Mugwanya et al, 2019 ; Koss et al, 2020 ). In addition, recent findings from the Combined HIV Adolescent PrEP and Prevention study (CHAPS) conducted in Uganda, Zimbabwe and South Africa indicate that even though young people were willing to use PrEP, there are barriers at individual, interpersonal, community, institutional and structural levels that require multi-level interventions to promote PrEP use ( Muhumuza et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Uganda, anticipated stockouts have also been reported as a barrier to PrEP uptake. 54 If not addressed, stockouts will continue to act as a primary barrier to PrEP scale-up in Cameroon. Sustainable funding, effective supply chain management, and inventory monitoring need to be strengthened to support effective PrEP implementation.…”
Section: Discussionmentioning
confidence: 99%